Arthrectomy for traumatic proximal interphalangeal arthritis in the lateral digit in a heifer - GOTO, A.; TSUZUKI, N.; KAJIHARA, A. tsuzuki@obihiro.ac.jp; MORIYAMA, T.; SASAKI, Y.; ZUSHI, N.; HATATE, K.; IINO, K.; YAMAGISHI, N. (Journal of the Hellenic Veterinary Medical Society, 2020)
Instructive information on the treatment for chronic deep infections of digital joints in a 9-month-old Holstein heifer is described in this report. Preoperative ultrasonographic and radiographic examinations revealed soft tissue swelling and subchondral bone lysis at the distal part of the proximal phalanx in the lateral digit. Arthrectomy was performed under xylazine sedation to remove infectious articular cartilage tissues. Immature callus formation was observed via radiography at the surgical site by the 28th postoperative day. On the 48th postoperative day, callus fell into disrepair on the radiographs along with aggravation of the locomotion score. After the application of a half-limb cast, the immature callus formed again by the 62nd postoperative day (11 months), and bony callus formation was observed by the 74th postoperative day. Thereafter, the heifer could walk well with marked improvement in the locomotion score. The withers height of the heifer at 13 months (136 cm) was within the range of that in control heifers of the same age on this farm (133 ± 3 cm); however, the body weight (BW) of this heifer (322 kg) was lower than the BW of controls (384 ± 26 kg). The BW gain from 11 to 13 months of age seemed to be higher in the present heifer (+76 kg) than in controls (+55±20 kg), suggesting that BW of the present heifer was returning to the original BW. Based on these observations, we suggested that arthrectomy was an effective treatment option for the present case of digital joint arthritis.